Organizational Citizenship Behavior as a Mediator of the Effects of Work Ability and Organizational Culture on Employee Performance - Yuliana Rosin Raga; Boge Triatmanto; Sina Setyadi (Journal of Innovative and Creativity, 2025)
The study purpose was to examine the influence of work ability and organizational culture on employee performance through Organizational Citizenship Behavior (OCB) among civil servants at ATR/BPN Malang Regency. The study aimed to determine whether work ability and organizational culture directly affect OCB and employee performance, as well as to analyze the mediating role of OCB in strengthening these relationships. This research provides insight into how internal competencies and cultural dynamics shape prosocial behaviors and performance outcomes within public-sector institutions. Materials and methods. This quantitative study employed a survey method using structured questionnaires distributed to 125 civil servants (PNS and PPPK). The variables measured included work ability, organizational culture, OCB, and employee performance. Instrument testing consisted of validity and reliability analyses, followed by classical assumption testing to ensure data quality. Hypothesis testing was conducted through multiple regression and path analysis to examine both direct and indirect effects. The Sobel test was used to validate the mediating role of OCB. Results. The findings indicate that work ability and organizational culture significantly influence OCB and employee performance. OCB also shows a significant positive effect on performance. Furthermore, OCB was found to mediate the relationship between work ability and performance, as well as between organizational culture and performance. These results suggest that employees with higher competence and strong cultural alignment are more likely to engage in voluntary behaviors that enhance their performance and organizational effectiveness. Conclusions. The study concludes that strengthening work ability and cultivating a positive organizational culture are essential strategies for improving employee performance in government institutions. OCB serves as a crucial behavioral mechanism that amplifies the impact of these factors. Enhancing OCB among employees can therefore contribute to greater productivity, better service delivery, and more effective achievement of organizational goals.